Studi Pendahuluan Karakteristik Habitat Ikan Hias Laut Endemik Banggai Cardinal Fish (Pterapogon kauderni) di Perairan Kota Baubau: Preliminary Study on Habitat Characteristics of Endemic Banggai Cardinal Fish Marine Ornamental Fish (Pterapogon kauderni) in Baubau City Waters (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
The Banggai dragonfly or better known as the Banggai Cardinal Fish (BCF) is an endemic fish originating from the waters of the Banggai Islands, Central Sulawesi. However, its distribution has been found, among others, in Bali waters, Ambon Bay, Kendari waters, Strait Lembeh and the Baubau City waters. The high demand from seawater ornamental fish collectors makes this species have high economic value, so this species is vulnerable to exploitation. This research was conducted due to the lack of information regarding the endemic species of BCF found in the Baubau City waters. Fish abundance data was collected using a visual census, that is the Line Intercept Transect (LIT) method. The length of the transect used is 50 meters with a coverage area of 2.5 meters to the left and 2.5 meters to the right. Water quality parameters were also taken to determine the suitability of the Banggai Cardinal Fish habitat in the Baubau City waters. The purpose of this study was to study the abundance and microhabitat of the BCF as preliminary information on the existence of this fish in Baubau City. The results of observations at 4 stations found a total population of 637 individuals/m2, which inhabits different microhabitat at each stasiun include: sea urchins, coral reefs, seagrasses and seaweed (Sargassum sp.). The introduced Banggai Cardinal Fish are able to adapt to new aquatic environments. The existence of this fish, especially in the waters of Baubau City, is expected to provide ecosystem services while still paying attention to its ecological function.